Public sectors' perception on critical relationship factors in IS/IT outsourcing: analysis of the literature and a Delphi examination. (1st January 2012) - Swar, Bobby; Moon, Junghoon; Khan, Gohar Feroz
The outsourcing of information system or information technology (IS/IT) in the public sector has become an accepted management practice recently. Despite of this increasing practice IS/IT outsourcing in the public sector has faced tough challenges resulting in failures of many of them. Researchers suggest a good relationship between the client and vendor as a vital requisite for the success of IS/IT outsourcing. In this regard, this study identifies and ranks the critical relationship factors in IS/IT outsourcing through the public sectors' perception using a 'ranking-type' Delphi method.